2010
DOI: 10.1161/circulationaha.109.898312
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mesenchymal Stem Cells Derived From Human Induced Pluripotent Stem Cells Attenuate Limb Ischemia in Mice

Abstract: Background— Aging and aging-related disorders impair the survival and differentiation potential of bone marrow mesenchymal stem cells (MSCs) and limit their therapeutic efficacy. Induced pluripotent stem cells (iPSCs) may provide an alternative source of functional MSCs for tissue repair. This study aimed to generate and characterize human iPSC-derived MSCs and to investigate their biological function for the treatment of limb ischemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
597
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 539 publications
(620 citation statements)
references
References 29 publications
14
597
1
8
Order By: Relevance
“…First, iPSC‐MSCs have a greater expansion capacity, maintaining differentiation potential and normal karyotypes for 120 doublings, while BM‐MSCs get senescent after 20 doublings 11. Second, BM‐MSCs may present reduced survival and differentiation ability when isolated from aged subject or patients with ageing‐related disorders 12, 13, 14, 15.…”
Section: Discussionmentioning
confidence: 99%
“…First, iPSC‐MSCs have a greater expansion capacity, maintaining differentiation potential and normal karyotypes for 120 doublings, while BM‐MSCs get senescent after 20 doublings 11. Second, BM‐MSCs may present reduced survival and differentiation ability when isolated from aged subject or patients with ageing‐related disorders 12, 13, 14, 15.…”
Section: Discussionmentioning
confidence: 99%
“…iPSC-MSCs could form mature mineralized structures that were histologically similar to mature bone, facilitating periodontal regeneration [39,40]. Transplanting iPSC-MSCs attenuated severe hindlimb ischemia and improved the hepatic function in mouse models [33,41,42]. These results suggested that iPSC-MSCs have high potential for tissue-engineering applications.…”
Section: Introductionmentioning
confidence: 86%
“…The iPSC lines were prepared from iPSCs, which were reprogrammed from human fibroblast cells, and differentiated into MSCs according to a previously described protocol [33]. Briefly, MSCs were purified by sorting for CD105 + /CD24 -cells and maintained in a medium containing 90% knockout Dulbecco's Modified Eagle's Medium (Gibco, Invitrogen Corporation, Carlsbad, CA) supplemented with 10% serum replacement medium (Gibco) and basic fibroblast growth factor (10 ng/mL; Gibco).…”
Section: Phenotypic Analysis Of Ipsc-mscsmentioning
confidence: 99%
See 2 more Smart Citations